2014
DOI: 10.1155/2014/235941
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Effects of Lead Nitrate on the Proliferation, Differentiation, and Gene Expression of Stem Cells Isolated from a Dental Origin

Abstract: Lead (Pb2+) exposure continues to be a significant public health problem. Therefore, it is vital to have a continuous epidemiological dataset for a better understanding of Pb2+ toxicity. In the present study, we have exposed stem cells isolated from deciduous and permanent teeth, periodontal ligament, and bone marrow to five different types of Pb2+ concentrations (160, 80, 40, 20, and 10 µM) for 24 hours to identify the adverse effects of Pb2+ on the proliferation, differentiation, and gene expression on these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…They threaten human health as they easily enter human body through the food chain. Lead (Pb 2+ ) is one of the most toxic heavy metals (Abdullah et al 2014). Lead moves into and throughout ecosystems and contaminate the vegetation, air, water and soil (Samal et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They threaten human health as they easily enter human body through the food chain. Lead (Pb 2+ ) is one of the most toxic heavy metals (Abdullah et al 2014). Lead moves into and throughout ecosystems and contaminate the vegetation, air, water and soil (Samal et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cell differentiation requires strict regulation of gene expression in order to ensure correct cell fate. Some studies report lead exposure impact on embryonic stem cells differentiation (Huang and Schneider, 2004; Abdullah et al, 2014; Senut et al, 2014). In a study involving embryonic stem cells cultivated with lead acetate 10 μM for 5 days, the authors observed significant proliferation inhibition in neurospheres collected from rat brain regions (Huang and Schneider, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Pb 2+ (50 ppm) exposure from conception to the age of 18 weeks reduced bone mass and promoted adipogenesis while decreasing osteogenesis in Long-Evans rats, in part through the inhi bition of the Wnt/β-catenin signaling pathway [74]. In vitro, exposure to higher levels o Pb 2+ (40-160 µ M) for 24 hours downregulated osteogenesis in hBM-MSCs and dental pulp stem cells [71]. In contrast, during the differentiation of 3T3-L1 fibroblasts, Pb 2+ treatmen at lower concentrations (5 and 10 µ M) for eight days increased lipid accumulation accom panied by the increase in mRNA expression of Pparγ and Plin1 [73], as well as C/ebpβ (a gene upstream of Pparγ) expression [73].…”
Section: Lead (Pb)mentioning
confidence: 99%
“…Pb 2+ not only shares the same ion transporter as Ca 2+ , but also acts as a competitive inhibitor of Ca 2+ when entering and leaving bone [70]. Exposure to Pb 2+ reduced femoral bone density in a rat model and inhibited osteoblastic activity in hBM-MSCs [71][72][73]. In vivo, Pb 2+ (50 ppm) exposure from conception to the age of 18 weeks reduced bone mass and promoted adipogenesis while decreasing osteogenesis in Long-Evans rats, in part through the inhibition of the Wnt/β-catenin signaling pathway [74].…”
Section: Lead (Pb)mentioning
confidence: 99%